Multi‐Functional Solid Additive Induced Favorable Vertical Phase Separation and Ordered Molecular Packing for Highly Efficient Layer‐by‐Layer Organic Solar Cells. Issue 44 (7th October 2021) - Yu, Runnan; Wu, Guangzheng; Cui, Yong; Wei, Xueqi; Hong, Ling; Zhang, Tao; Zou, Chao; Hu, Siqian; Hou, Jianhui; Tan, Zhan'ao
Abstract: Layer‐by‐layer (LBL) deposition strategy enabling favorable vertical phase distributions has been regarded as promising candidates for constructing high‐efficient organic photovoltaic (OPV) cells. However, solid additives with the merits of good stability and reproducibility have been rarely used to fine‐tune the morphology of the LBL films for improved efficiency and stability. Herein, hierarchical morphology control in LBL OPV is achieved via a dual functional solid additive. Series of LBL devices are fabricated by introducing the solid additive individually or simultaneously to the donor or acceptor layer to clarify the functions of additives. Additive in the donor layer can facilitate the formation of preferable vertical component distribution, and that in the acceptor layer will enhance the molecular crystallinity for better charge transport properties. The optimized morphology ultimately contributed to high PCEs of 16.4% and 17.4% in the binary and quaternary LBL devices. This reported method provides an alternative way to controllably manipulate the morphology of LBL OPV cells. Abstract : Hierarchical morphology modifications in layer‐by‐layer organic solar cells are achieved by a multi‐functional volatile solid additive, yielding favorable vertical component distribution and molecular packing. This work realizes simultaneous improvements in device efficiency and stability, providing a practical method for morphology control in layer‐by‐layer devices.